ADMINISTRATIVE SYSTEM AT THE SURABAYA CITY NATIONAL ZAKAT COLLECTION AGENCY OFFICE - Irsyad Wulidal Habib Arroihan; Airlangga Bramayudha (BAIK Publishers, 2026)
This study aims to describe the administrative system and administrativemanagement practices implemented at the Surabaya City National Zakat Agency (BAZNAS) Office. This study uses a qualitative approach with a descriptive design. Research data were obtained through interviews, observations, and documentation involving administrative staff and leadership elements who play a role in institutional administrative management. The results of the study indicate that the administrative system at the Surabaya City BAZNAS Office has been organized in a structured manner through recording, archiving, and document management mechanisms in accordance with applicable administrative management procedures. The use of information technology has begun to be integrated to support office administrative activities,although in practice there is still a reliance on manual systems and limited coordination and integration between departments. This study concludes that the administrative system at the Surabaya City BAZNAS Office has been running quite well, but still requires strengthening aspects of digital-based administrative management and improving internal coordination so that administrative implementation can be more effective and sustainable.